Concise synthesis and CDK/GSK inhibitory activity of the missing 9-azapaullones - CONNON, STEPHEN; GRAYSON, DAVID; POWER, DAVID PATRICK (My University, 2010)
A remarkably concise, chromatography-free route to the parent compound of the paullone family of cyclin-dependent kinase (CDK) inhibitors is reported. A similar strategy allowed the synthesis of the hitherto missing 9-azapaullone and its protonated, N-oxidised and N-alkylated derivatives. Screening studies identified an active and strongly selective inhibitor of CDK9/cyclin T
PUBLISHED
Keywords: Biochemistry; Cyclin Dependent Kinases; Cancer; Neuroscience